Teaching Hurricane María: From Chaos and Crisis to Healing and Resistance in Contemporary Puerto Rican Fiction - Diana Aramburu (Studies in 20th & 21st Century Literature, 2026)
In my years of teaching, one of the questions that keeps coming up for me is how do instructors teach students about different crises? How can we investigate crises, like immigration or gender violence crises or the aftermaths of natural disasters, through fiction? How can we encourage students to analyze these events or these more generalized crises through fiction, especially when in some cases, students were too young to remember or in other cases, catastrophic natural disasters, like Hurricane María in 2017 that devastated Puerto Rico, did not directly impact them in the United States? This article studies pedagogical and methodological approaches to teaching representations of trauma following natural disasters, in particular the aftereffects of Hurricane María in contemporary Puerto Rican fiction at the University of California, Davis. By analyzing literary and artistic responses to the catastrophic storm (i.e. literature, films, photography, and music, among others) as well as the political activism that has occurred in response to an inefficient and negligent Puerto Rican government, students at UC Davis engaged with fiction that not only illustrates chaos and crisis, but that also heals, resists, and decolonizes. In detailing how I foster student engagement employing multimodal and multigeneric approaches in my After Hurricane María: From Chaos to Rebellion in Contemporary Puerto Rican Fiction, I propose that teaching crisis and trauma fiction can promote students’ critical thinking, allowing them to gain a better understanding of contemporary iterations of crisis while being mindful of their own wellbeing. Using a trauma-informed educational practice and approach, I encouraged my students to analyze not only how artists are using visual and written material to represent crises and their aftereffects, but also how we use art, literature, and other mediums to examine and respond to the effects of crisis on our lives and heal from trauma.
Keywords: Contemporary Puerto Rican Fiction; Hurricane María; teaching natural disasters; teaching trauma; trauma-informed pedagogy; crisis fiction; trauma narratives